Prospective and retrospective analysis of the sporting success of elite Spanish high and long jumpers - Rodriguez-Gomez, P.; Gallo-Salazar, C.; Salinero, J. J. (Journal of Human Kinetics, 2024)
The aim of the present study was to analyze the sporting progression from U14 to senior categories of elite Spanish high and long jumpers. For prospective analysis, 300 athletes ranked top 20 at U14 were analyzed (153 female and 147 male). For retrospective analysis, 64 athletes ranked in the top 20 in the senior category were included (21 female and 43 male). Ranking positions were registered in each of the seasons where they presented records. Only 6.3% (19) of athletes who reached the top 20 at U14 became successful senior athletes [4.7% (14) of athletes maintained top 20 status throughout their sporting careers from U14 to senior]. The transition rate from U14 to U16 (35.7%) was the most severe drop down in consecutive categories (after this, it ranged from 47.8 to 66.7%). Of the senior top 20 athletes (64), most of them were already ranked top 20 at U16 (59.4%, 38), at U18 (62.5%, 40), at U20 (70.3%, 45) and at U23 (78.1%, 50). Nevertheless, only 34.4% (22) were top 20 when they were U14 athletes. Transition rates in the top 20 senior athletes ranged from 86.7 to 95.5%. Around one out of four (26.6%, 17) of the top 20 senior athletes maintained top 20 status throughout their sporting careers from U14 to the senior category. Although early success is not a good predictor of senior success, successful senior athletes excelled early on and were able to remain in top rankings throughout their sporting careers of national elite jumpers.